AL-QUR’AN DAN BERBUAT BAIK (Kajian Tematik Term “Al-Birr”) - Abdullah, Dudung (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2018)
In the Qur'an there is the term al-Birr. Al-Birr means doing good orvirtue. Humans make as much effort as possible and as good as possible in doing good. Man in performing the virtue by emulatingAllah swt. "The Most Beneficent" (Al-Barru). Of the many goodperforming models can be summarized in the three main areas,namely the field of faith, the field of worship, and the field ofmorality.